PEMAKNAAN KHALAYAK TERHADAP KONSTRUKSI PERAN BAPAK RUMAH TANGGA dalam ANIME “THE WAY OF THE HOUSEHUSBAND (極主夫道, GOKUSHUFUDŌ)” - Salsabila Alfi Rizq Putri; Hapsari Dwiningtyas Sulistyani; Muhammad Bayu Widagdo (Interaksi Online, 2023)
Pandemic era forced Indonesia’s society to faced social change that shown shifting roles in family division. However, househusband’s existence become a problem due to its role ambiguity that against patriarchal gender norms. On the other hand, this ambiguity become an interesting aspect on an anime called The Way of the Househusband. This anime served unique representation of a househusband that utilize Yakuza way to do his role which attract many Indonesian audiences. The aim of this research is to find audiences’ reception towards construction of househusband in this anime. This research conducted codes of television to analyses the anime and then interpret audiences’ reception using Hall’s decoding positions. Preferred reading of this anime represents characteristics of a househusband and humanity side of Yakuza. Ideology of this anime wanted to normalize men that capable on homemaking roles and offered househusband as an alternative role. This research able to found various reception of young adults’ audiences. They accepted househusband as a well-function role in homemaking. Some audiences open possibilities to be a househusband or have a househusband as a partner. Although, audiences prefer to become a double-income couple. The construction of an ex-Yakuza househusband characteristics is able to be accepted by audiences as an ideal type of a househusband. However, some audiences perceived househusband task is not realistic due to perception that homemaking is a collaborative role for each family members. Audiences also accepted the ideology that put househusband and salaryman in the same place, their difference only on their role, traits, and knowledge about house and family matters. Research findings shown role tunning pattern that uncover how audiences’ attitudes towards househusband’s role is affected by conversation’s context and how well audiences recognize the person who’s a househusband.